The Development Impact of a Best Practice Seasonal Worker Policy - Gibson, John; McKenzie, David (The Review of Economics and Statistics, 2014)
Seasonal migration programs are widely used around the world, yet there is little evidence as to their development impacts. A multiyear prospective evaluation of New Zealand's Recognised Seasonal Employer (RSE) seasonal worker program allows us to measure the impact of participating in this program on households in Tonga and Vanuatu. Using a propensity-score prescreened difference-in-differences analysis based on surveys fielded before, during, and after participation, we find that the RSE has indeed had positive development impacts that dwarf those of other popular development interventions. It has increased income, consumption, and savings of households; durable goods ownership; and subjective standard of living. The results also suggest that child schooling improved in Tonga.